A Brief Note on Bus Based Evacuation Planning - Thapa, Bam Bahadur; Khadka, Shree Ram (Journal of Institute of Science and Technology, 2016)
Evacuation route planning is essential for emergency preparedness, especially in regions threatened by hurricanes, earthquake etc. The evacuees who do not travel on their own are gathered at few collection points, where they are brought on buses to take them to safe region in bus based evacuation. Bus based evacuation planning is more essential for developing country like Nepal. It is necessary to reach the destination as early as possible for bus based evacuation. The bus based evacuation planning (BEP) problem is a variant of vehicle routing problem that arises in emergency planning. The problem in this variant is that not all the evacuees can gather at the same time, elderly and handicaps may need special help like wheelchair and may need more pickup time. Another problem is that at the shelter, some people may need special care like medicine, oxygen etc. In this paper we review a mathematical model to minimize the duration of evacuation together with the dynamic programming and the branch and bound as solution procedures. Moreover, a brief report of a case study for Kathmandu has also been given. Journal of Institute of Science and Technology Volume 21, Issue 1, August 2016, page: 28-34